Development and design of the Ateneo Library Women's Writing information retrieval system (AIRS) - Bautista, Marie Edelquin D. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Archives are kept by numerous archival facilities since it contains permanent and historical value. Organizing and providing access to these archives are two different important issues that needed a careful consideration. Currently, organization and classification are evenly implemented by the archival institutions with the help of the available archival standards. However, providing easy access to these archives, especially in the Philippines, is still a struggle with most of the archival facilities. One of which is the Ateneo Library of Women's Writings or ALiWW: an archival facility that was established in the year 1994. Currently, there is a need to provide an easy access to the ALiWW collection in order to increase its utilization and awareness in the community it belongs.